Public awareness and support for endangered tree species protection- a focus on Dipterocarpus semivestitus in UiTM Seri Iskandar Perak Malaysia - Jaafar Sidek, Muhammad Zulfikry; Hamzah, Helmi (2025)
The critically endangered status of Dipterocarpus semivestitus as identified by the International Union for Conservation of Nature (IUCN) highlights the urgent need for conservation efforts. Despite its critical status, public awareness and support for the preservation of this species remain unclear. This study investigates the level of public awareness and support for the conservation of Dipterocarpus semivestitus, focusing on the communities of Seri Iskandar, Perak. The research aims to provide insights into the public awareness and support in its conservation efforts. The study adopted a quantitative approach, analyzing 120 responses from the Seri Iskandar, Perak community, covering multiple residential areas.The results reveal that biodiversity importance garnered the highest level of awareness, while cultural significance and conservation efforts received the lowest awareness among the Seri Iskandar community. These insights could guide stakeholders and policymakers in developing effective strategies to promote the protection of Dipterocarpus semivestitus and other endangered tree species.